Morphing Planar Graphs in Spherical Space - Kobourov, Stephen; Landis, Matthew (Journal of Graph Algorithms and Applications, 2008)
We consider the problem of intersection-free planar graph morphing,and in particular, a generalization from Euclidean space to sphericalspace. We show that there exists a continuous and intersection-freemorph between two sphere drawings of a maximally planar graph,provided that both sphere drawings have convex inscribed polytopes,where sphere drawings are the spherical equivalent of plane drawings:intersection-free geodesic-arc drawings. In addition, we describe amorphing algorithm along with its implementation. Movies of samplemorphs can be found athttp://smorph.cs.arizona.edu. <!---->